MsFLASH participants' priorities for alleviating menopausal symptoms. (2nd November 2015) - Carpenter, J. S.; Woods, N. F.; Otte, J. L.; Guthrie, K. A.; Hohensee, C.; Newton, K. M.; Joffe, H.; Cohen, L.; Sternfeld, B.; Lau, R. J.; Reed, S. D.; LaCroix, A. Z.
ABSTRACT: Objective To describe self-reported menopausal symptom priorities and their association with demographics and other symptoms among participants in an intervention trial for vasomotor symptoms (VMS). Methods Cross-sectional study embedded in the MsFLASH 02 trial, a three-by-two factorial design of yoga vs. exercise vs. usual activity and omega-3-fatty acid vs. placebo. At baseline, women ( n  = 354) completed hot flush diaries, a card sort task to prioritize symptoms they would most like to alleviate, and standardized questionnaires. Results The most common symptom priorities were: VMS ( n  = 322), sleep ( n  = 191), concentration ( n  = 140), and fatigue ( n  = 116). In multivariate models, women who chose VMS as their top priority symptom ( n  = 210) reported significantly greater VMS severity ( p  = 0.004) and never smoking ( p  = 0.012), and women who chose sleep as their top priority symptom ( n  = 100) were more educated ( p  ≤ 0.001) and had worse sleep quality ( p  < 0.001). ROC curves identified sleep scale scores that were highly predictive of ranking sleep as a top priority symptom. Conclusions Among women entering an intervention trial for VMS and with relatively low prevalence of depression and anxiety, VMS was the priority symptom for treatment. A card sort may be a valid tool for quickly assessing symptom priorities in clinical practice and research.